Clinical Characteristics, Risk Factors, and Outcomes of Carbapenem-Resistant Enterobacteriaceae Infection among Patients Hospitalized in the US Military Health System. (4th October 2017) - Adams, Daniel; Susi, Apryl; Nylund, Cade
Abstract: Background: Data on the epidemiology and impact of carbapenem-resistant Enterobacteriaceae (CRE) infections in hospitalized populations are limited. We aimed to characterize the epidemiology, identify risk factors, and measure outcomes of CRE infections among patients hospitalized in the US military health system (MHS). Methods: We performed a retrospective study of hospitalized patients with CRE infection using billing records from the US MHS database. Cases included patients admitted to a US or overseas military treatment facility for ≥2 days from October 2008 to September 2015 with a clinical culture growing any Enterobacteriaceae reported as resistant to a carbapenem. Multivariable logistic regression was used to identify comorbid conditions and procedures associated with CRE infection, and a high-dimensional propensity score calculation was performed to evaluate in-hospital mortality, length of stay and hospitalization costs. Results: From 1, 162, 666 hospitalized patients in the MHS, we identified 153 (0.013%) with CRE infection over the 7-year study period. CRE infections consisted mostly of urinary tract infections (31.8%), respiratory tract infections (22.0%), and wound/skin and soft-tissue infections (13.9%), and CRE isolates exhibited significant cross-resistance to alternate antibiotics. Risk factors for CRE infection included procedures involving manipulation of the gastrointestinal tract, trauma, and orthopedic procedures, and critical illness such as septicemia, shock, and aspiration pneumonitis. Patients hospitalized with CRE infection had significantly higher hospitalization costs (attributable difference [AD] 176, 517, P < 0.0001), longer hospital stays (AD 27.8 days, P < 0.0001), and were more likely to die in the hospital (odds ratio 4.77; 95% confidence interval 2.68–8.48). Conclusion: CRE are a significant threat to patients hospitalized in the US MHS, given their impact on hospitalization duration, costs, and mortality. Active surveillance for CRE colonization and infection should be considered for high-risk populations. Given the lack of effective antibiotics to combat CRE infection, research into novel therapeutics and antimicrobial stewardship efforts are critically important. Disclosures: All authors: No reported disclosures.